The Social Mobility Commission, State of the Nation 2022: A Fresh Approach to Social Mobility. A commentary - Bukodi, E; Goldthorpe, JH (Wiley, 2022)
The Social Mobility Commission's most recent annual report is entitled State of the Nation 2022: A Fresh Approach to Social Mobility. We examine what in the report is new, whether explicitly or implicitly, and how far the newness serves to enhance our understanding of social mobility in Britain today and is of relevance to problems and policy issues that arise. We find that the supposed greater attention to the findings of academic research is selective and, overall, quite limited; that the proposed new focus on ‘small steps upwards’ shifts attention away from what are the most serious and enduring instances of inequality of opportunity in British society; that the emphasis on individual agency as a means of overcoming disadvantaged social origins neglects the role of agency in maintaining inequality in mobility chances; and that the determinedly upbeat tone of the report raises questions of the independence of the Social Mobility Commission, under its present leadership, as a body charged with holding governments to account in their efforts to ensure that ‘the circumstances of birth do not determine outcomes in life’.